Social Media Analysis of Kang Dedi Mulyadi's Instagram Account In Managing Digital Advertising And Persona Branding Using The Peso Model - Fahmi, Akbar Fajarudin; Tomasowa, Gloria Angelita (Eastasouth Institute, 2025)
This study aims to analyze the digital advertising management strategy and personal branding of Kang Dedi Mulyadi (KDM) through his Instagram account, using the PESO (Paid, Earned, Shared, Owned) model. This topic is important because it demonstrates the dynamics of digital political communication in the era of increasingly personal and culture-based social media. The research method used is a qualitative approach with descriptive analysis of KDM's Instagram content. The results show that KDM succeeded in building authentic digital communication through emotional narratives, strong visuals, and the use of local language and a Sundanese Buhun cultural approach. This strategy does not rely on paid promotions, but relies on the organic power of humanistic and socially relevant content. In addition, this study recommends the development of the PESO model by adding Cultural Capital Media elements to adapt to the context of Indonesian political communication which is rich in local cultural values. In conclusion, KDM's success demonstrates the importance of culture-based content and emotional closeness in strengthening the effectiveness of digital political communication on social media.